Are Health Insurance Markets Competitive? - Dafny, Leemore S. (The American economic review, 2010)
To gauge the competitiveness of the group health insurance industry, I investigate whether health insurers charge higher premiums, ceteris paribus, to more profitable firms. Such "direct price discrimination" is feasible only in imperfectly competitive settings. Using a proprietary national database of health plans offered by a sample of large, multisite firms from 1998–2005, I find firms with positive profit shocks subsequently face higher premium growth, even for the same health plans. Moreover, within a given firm, those sites located in concentrated insurance markets experience the greatest premium increases. The findings suggest health care insurers are exercising market power in an increasing number of geographic markets.